THE Video Dubbing Projects in English: Verb Students - Zubury, Nurul Fauziah; Jumiaty, Andi Asri; Maharida (FKIP Unismuh Makassar, 2026)
This study investigates the effectiveness of video dubbing projects in improving vocational students’ English verb vocabulary. Addressing the persistent challenge of limited contextual vocabulary acquisition, this research introduces dubbing as an interactive, multimodal learning strategy. A pre-experimental design was employed with 37 eleventh-grade students at SMAK Makassar using total sampling. Data were collected through pre-test and post-test measures. Results show a substantial improvement in students’ verb vocabulary, with mean scores increasing from 42.97 to 78.37. Statistical analysis indicates significance (p = 0.01 < 0.05), confirming the effectiveness of the intervention. The novelty of this study lies in integrating audiovisual translation tasks to promote active vocabulary use in context. This research contributes empirical evidence supporting video dubbing as an engaging pedagogical tool that enhances comprehension, retention, and practical usage of verbs in vocational English learning environments.